2015
DOI: 10.4028/www.scientific.net/amm.754-755.300
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Hydroxide (NaOH) Concentration on Compressive Strength of Alkali-Activated Slag (AAS) Mortars

Abstract: Energy saving in building technology is among the most critical problems in the world. Thus it is a need to develop sustainable alternatives to conventional concrete utilizing more environmental friendly materials. One of the possibilities to work out is the massive usage of industrial wastes like ground granulated blast furnace slag (GGBS) to turn them to useful environmental friendly and technologically advantageous cementitious materials. In this study, ground granulated blast furnace slag (GGBS) is used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…[13] The research conducted by Tajunnisa stated that more irregular shape particles required more water in mixing geopolymer paste [8].With the purpose of produce geopolymer paste, water content is represented by alkali solution. It is also concluded that concentration and composition of alkali solution plays an important role in developing mechanical properties of geopolymer paste [20][21][22].…”
Section: Sem Testmentioning
confidence: 99%
“…[13] The research conducted by Tajunnisa stated that more irregular shape particles required more water in mixing geopolymer paste [8].With the purpose of produce geopolymer paste, water content is represented by alkali solution. It is also concluded that concentration and composition of alkali solution plays an important role in developing mechanical properties of geopolymer paste [20][21][22].…”
Section: Sem Testmentioning
confidence: 99%
“…The results of the mechanical properties (Figure 4) show that low concentration sodium hydroxide -Torgal et al, 2008;Thunuguntla and Gunneswara Rao, 2018). However, an excess of alkali has detrimental effects hindering the formation of the alkali activation reaction products (Pacheco-Torgal et al, 2008;Hashim et al, 2015).…”
Section: Optimization Of the Cobindermentioning
confidence: 99%
“…Using fly ash as a choice in making geopolymer technology is one of many inventions to decrease by-product piling in power plants. Geopolymer binder is formed by mixing fly ash with alkali solution, where sodium hydroxide (NaOH) with a concentration of 8 to 16 molar is applied [3,4]. Other than NaOH, sodium silicate (Na2SiO3) is also mixed to enrich soluble silica in the binder system, where the fly ash usually contains less reactive silica than other alumina-silica source e.g.…”
Section: Introductionmentioning
confidence: 99%